Diseño y construcción de un sistema de control y monitoreo para el suministro eléctrico del variador de frecuencia SINAMIC G110 por me4dio del PLC X LOGICSOFT vía SMS. - Ortiz Valdez, Fredy Fabricio (2014)
In developing the thesis was designed and built a didactical board to perform the monitoring for the electric supply of the inverter SINAMIC G110, through PLC XLOGICSOFT with a communication module via SMS. the implemented monitoring design shall allow to receive a notice of flaw via MSM, according to the configuration that implement to PLC which will send a msn to cell phone when there is an interruption at the power supply, the installed teams are flexible and with programming times relatively shorts, depending on user requirements